Protective effect of Brassica oleracea var. botrytis L. against theophylline-induced hepatocellular abnormalities in rats - Endang Sri Sunarsih; Lukman Hakim; Sugiyanto Sugiyanto; Sumantri Sumantri (Faculty of Medicine, Universitas Trisakti, 2012)
BackgroundIndole and its derivatives, such as indole acetic acid are active constituents of cauliflower (Brassica oleracea var. botrytis L.) with are known to function as plant growth hormones. Drug metabolism mainly occurs in the liver, so that the possibility of damage to this organ is considerable. The purpose of this study was to evaluate the effect of cauliflower extract on alanine transaminase (ALT) levels and on the hepatocyte morphology induced by theophylline in Wistar rats.MethodsTwenty Wistar rats were divided randomly into four groups. Group I was given only theophylline 20 mg/kg BW. Groups II, III, and IV were given cauliflower extract 200 g/kg BW, for 5, 10, 15 days, and on the last day were given theophylline 20 mg/kg BW. On days 5, 10, and 15 the animals were terminated, their livers taken and observed for microscopic appearance, while blood samples were taken for measuring ALT levels.ResultsCauliflower affected a reduction in ALT levels, mean serum ALT concentration in rats given cauliflower for 5 days (109.86 ± 2.20 IU/L was significant higher compared to rats given cauliflower for 15 days (71.58 ± 3.17 IU/L) (p=0.000). Mean values of histopathologic liver cells in rats given cauliflower for 15 days (1.17 ± 0.01) significant lower compared to rats given cauliflower for 5 days (1.45 ± 0.06) (p=0.000).ConclusionSCauliflower extract reduced the level of ALT and improved the microscopic appearance of hepatic cells in the rats. Cauliflower extract could lead to the development of potent anti-tumor agents for hepatic cancer treatment.